Multi-element solid waste-based cementing material and preparation method thereof
Through specific raw material ratios and particle grading, the pore structure of multiple solid waste-based gelling materials is adjusted, and the problem of insufficient mechanical properties of existing materials is solved, and higher mechanical properties and durability are achieved.
Patent Information
- Application Number
- CN202510056751.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The pore structure of existing multi-purpose solid waste-based gelling materials is not rich enough, which affects its mechanical properties.
By using specific raw material ratios and particle grading, including fly ash, sea silt, desulfurization gypsum, glass fiber, slag, cement and rice husk ash, the particle size range of the material is adjusted to enrich the pore structure of the cemented material.
It improves the mechanical properties and durability of the gelled materials, and enhances the compactness and compression and flexural resistance of the materials.
Smart Images

Figure BDA0005241652830000111
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of building materials, and in particular to a multi-solid waste-based cementitious material and a preparation method thereof. Background Art
[0002] Multi-solid waste-based cementitious materials are new cementitious materials made from a variety of industrial solid wastes as the main raw materials through a series of fine processing and chemical reactions. Its uniqueness lies in the ability to transform these materials, which were originally regarded as waste, into new building materials with high added value and broad application prospects. In terms of preparation methods, multi-solid waste-based cementitious materials adopt advanced theories of complex salt effect and silicon's four-coordination isomorphism effect. Through scientific proportions and precise processing technology, various solid wastes are synergistically activated, thereby preparing hydraulic cementitious materials with excellent performance.
[0003] In the related art, a multi-component solid waste cementitious material is disclosed, which includes the following raw materials in the following weight proportions: 23-25 parts of fly ash, 10-12 parts of carbide slag, 5-9 parts of desulfurized gypsum, 10-20 parts of steel slag, 12-14 parts of slag, and 25-30 parts of cement. The average particle size of the raw materials used is 8-10 microns. By using solid waste and reducing the particle size of the raw materials by physical and mechanical grinding, the respective cementitious activity is stimulated and the utilization rate of solid waste is improved.
[0004] However, the average particle size of all raw materials is 8-10 μm, which may lead to an insufficiently rich pore structure of the cementitious material and affect its mechanical properties. Summary of the invention
[0005] In order to improve the mechanical properties of solid waste-based cementitious materials, the present application provides a multi-component solid waste-based cementitious material and a preparation method thereof.
[0006] In the first aspect, the present application provides a multi-solid waste-based cementitious material, which adopts the following technical solution:
[0007] A multi-solid waste-based cementitious material comprises the following raw materials in parts by weight: 20-25 parts of fly ash, 10-14 parts of sea silt, 6-10 parts of desulfurized gypsum, 2-5 parts of glass fiber, 12-14 parts of slag, 25-30 parts of cement, and 10-15 parts of rice husk ash; the particle size of the slag is 12-15 μm, the particle size of the sea silt and desulfurized gypsum is 8-10 μm, and the particle size of the fly ash and rice husk ash is 3-6 μm.
[0008] By adopting the above technical scheme, fly ash can react with calcium hydroxide in cement to generate a gel material with higher strength. Rice husk ash is the residue after burning rice husks. It has a high specific surface area and rich siliceous components. The siliceous components can react with calcium hydroxide in cement to generate more gel material. The high specific surface area of rice husk ash can provide more reaction interfaces and better combine with fly ash and cement. Sea silt is rich in organic matter, salt and clay minerals, which helps to improve the workability, corrosion resistance and plasticity of cementitious materials, thereby improving the later strength of cementitious materials. Glass fiber can form a three-dimensional network structure inside the material, effectively disperse and transfer stress, prevent the generation and expansion of cracks, and thus improve the durability of cementitious materials. Desulfurized gypsum can adjust the setting time of cementitious materials to ensure the smooth progress of the construction process. Slag can undergo secondary hydration reaction with calcium hydroxide in cement to generate more hydration products, fill the pores inside the material, and improve the density of cementitious materials. Moreover, the particle grading of the above-mentioned materials can enrich the pore structure of the cementitious material. Therefore, the present application helps to improve the mechanical properties and durability of the cementitious material by adopting the above-mentioned raw material ratio and particle grading.
[0009] In a specific embodiment, the rice husk ash is prepared according to the following steps:
[0010] The rice husk is kept at 400-500°C for 20-25 minutes, heated to 600-700°C, kept for 50-70 minutes, heated to 750-850°C, kept for 20-30 minutes, cooled naturally, and the ashes are collected;
[0011] The ash was ball-milled to obtain rice husk ash with a particle size of 3-6 μm.
[0012] By adopting the above technical solution, the rice husk gradually dries and begins to carbonize at 400-500℃. 600-700℃ is the main stage of rice husk combustion, in which most of the organic matter will be completely burned at this temperature. Then raising the temperature to 750-850℃ will help the rice husk to be completely ashed and reduce the residual carbon content. Finally, ball milling can be performed to obtain rice husk ash within the required particle size range.
[0013] In a specific embodiment, any one of carbonate or bicarbonate is mixed evenly with rice husk and then burned at 400-500°C.
[0014] By adopting the above technical solution, when rice husks are mixed with carbonates or bicarbonates and burned, as the temperature rises, the carbonates or bicarbonates will undergo thermal decomposition and release carbon dioxide gas. Since these gases are generated inside the rice husk ash and expand rapidly, they will exert pressure on the surrounding rice husk ash, thereby forming small holes or bubbles. The rice husk itself will also release some gases, such as water vapor, carbon dioxide, etc. during the combustion process. When rice husks are burned with carbonates or bicarbonates, the release of these gases will be accelerated and enhanced, further promoting the formation of a porous structure, making the rice husk ash more loose and porous, which helps to increase the specific surface area of the rice husk ash. Rice husk ash with a high specific surface area has extremely high activity and adsorption capacity, and can effectively combine with other components in the cementitious material, thereby improving the overall strength and durability of the material.
[0015] In a specific embodiment, the multi-solid waste-based cementitious material further includes diatomaceous earth.
[0016] By adopting the above technical solution, diatomite has a unique porous structure and a high specific surface area. By physically or chemically combining with gel material, diatomite can improve the mechanical properties of the material such as compression and flexural resistance, making the material more durable. In addition, diatomite has good adsorption properties and chemical stability, and can effectively absorb and fix free water and harmful substances in the gelling material, thereby reducing the internal defects and corrosion risks of the material.
[0017] In a specific embodiment, the multi-solid waste-based gelling material further includes cellulose ether.
[0018] By adopting the above technical solution, cellulose ether can form a denser microstructure with rice husk ash and diatomaceous earth, enhancing the mechanical properties and durability of the material. In addition, cellulose ether can enhance the water retention and workability of the material, making the construction smoother and reducing problems such as cracking and shrinkage.
[0019] In a specific embodiment, the multi-solid waste-based gelling material further includes a bubbling agent.
[0020] By adopting the above technical solution, the bubbling agent can form evenly distributed bubbles inside the material, and these bubbles can effectively improve the pore structure of the material, reduce the density, and optimize the mechanical properties of the material.
[0021] In a specific embodiment, the bubbling agent includes aluminum hydroxide, soy protein powder and sodium dodecylbenzene sulfonate in a weight ratio of 1:(0.1-0.2):(5-8).
[0022] By adopting the above technical solution, the present application has found through experiments that the multi-solid waste-based gelling material obtained by using the foaming agent with the above raw material ratio has better mechanical properties. This may be because aluminum hydroxide can improve the high temperature resistance of the gelling material, and the aluminum oxide produced when it decomposes can also enhance the hardness of the material. The amino acids in soy protein powder can react chemically with other components in the gelling material to form a more stable structure. Sodium dodecylbenzene sulfonate can effectively reduce the surface tension of the material, making it easier for bubbles to form and stabilize in the material, thereby controlling the pore structure and density of the material. Therefore, it helps to improve the mechanical properties of multi-solid waste-based gelling materials.
[0023] In a specific embodiment, the multi-solid waste-based gelling material further includes a silane coupling agent.
[0024] By adopting the above technical solution, the coupling agent can enhance the interfacial bonding force between the glass fiber and the matrix material, thereby improving the mechanical properties of the multi-solid waste-based cementitious material.
[0025] In the first aspect, the present application provides a method for preparing a multi-solid waste-based cementitious material, which adopts the following technical solution:
[0026] A method for preparing a multi-solid waste-based gelling material comprises the following steps:
[0027] The fly ash, sea silt, desulfurized gypsum, slag, cement and rice husk ash are respectively ball-milled to obtain slag with a particle size of 12-15 μm, sea silt and desulfurized gypsum with a particle size of 8-10 μm, and fly ash and rice husk ash with a particle size of 3-6 μm;
[0028] The fly ash, sea silt, desulfurized gypsum, slag, cement, rice husk ash and glass fiber are evenly mixed to obtain a multi-solid waste-based cementitious material.
[0029] In summary, this application has the following beneficial effects:
[0030] 1. This application uses sea silt, glass fiber, rice husk ash and specific particle grading to enrich the pore structure of cementitious materials and improve the mechanical properties and durability of cementitious materials.
[0031] 2. The present application also uses diatomaceous earth and cellulose ether, which can form a denser microstructure and further enhance the mechanical properties and durability of the material.
[0032] 3. The present application also uses a bubbling agent or a silane coupling agent to control the pore structure and density of the material and enhance the interfacial bonding force between the glass fiber and the matrix material, which helps to improve the mechanical properties of the multi-solid waste-based cementitious material. DETAILED DESCRIPTION
[0033] The present application is further described in detail below in conjunction with embodiments and comparative examples.
[0034] Example
[0035] Example 1
[0036] The present embodiment provides a multi-solid waste-based cementitious material, including the following raw materials: 23 kg of fly ash, 12 kg of sea silt, 8 kg of desulfurized gypsum, 4 kg of glass fiber, 13 kg of slag, 27 kg of cement, and 13 kg of rice husk ash; the particle size of the slag is 12-15 μm, the particle size of the sea silt and the desulfurized gypsum is 8-10 μm, and the particle size of the fly ash and the rice husk ash is 3-6 μm.
[0037] Wherein, rice husk ash is prepared according to the following steps:
[0038] Put the rice husk into the furnace, heat it to 450℃, keep it warm for 22 minutes, then heat it to 650℃, keep it warm for 60 minutes, then heat it to 800℃, keep it warm for 25 minutes, cool it naturally, and collect the ash.
[0039] The ash was ball-milled to obtain rice husk ash with a particle size of 3-6 μm.
[0040] This embodiment also provides a method for preparing a multi-solid waste-based gelling material, comprising the following steps:
[0041] Fly ash, sea silt, desulfurized gypsum, slag, cement and rice husk ash are respectively ball-milled to obtain slag with a particle size of 12-15 μm, sea silt and desulfurized gypsum with a particle size of 8-10 μm, and fly ash and rice husk ash with a particle size of 3-6 μm.
[0042] The fly ash, sea silt, desulfurized gypsum, slag, cement, rice husk ash and glass fiber are evenly mixed to obtain a multi-solid waste-based cementitious material.
[0043] Example 2
[0044] The only difference between this embodiment and Embodiment 1 is that the multi-solid waste-based cementitious material includes the following raw materials: 20 kg fly ash, 14 kg sea silt, 10 kg desulfurized gypsum, 5 kg glass fiber, 14 kg slag, 25 kg cement, and 15 kg rice husk ash.
[0045] Example 3
[0046] The only difference between this embodiment and Embodiment 1 is that the multi-solid waste-based cementitious material includes the following raw materials: 25 kg fly ash, 10 kg sea silt, 6 kg desulfurized gypsum, 2 kg glass fiber, 12 kg slag, 30 kg cement, and 10 kg rice husk ash.
[0047] Example 4
[0048] The only difference between this embodiment and embodiment 1 is that rice husk ash is prepared according to the following steps:
[0049] Put the rice husk into the furnace, heat it to 400℃, keep it warm for 25min, then heat it to 600℃, keep it warm for 70min, then heat it to 750℃, keep it warm for 30min, cool it naturally, and collect the ash.
[0050] The ash was ball-milled to obtain rice husk ash with a particle size of 3-6 μm.
[0051] Example 5
[0052] The only difference between this embodiment and embodiment 1 is that rice husk ash is prepared according to the following steps:
[0053] Put the rice husk into the furnace, heat it to 500℃, keep it warm for 20 minutes, then heat it to 700℃, keep it warm for 50 minutes, then heat it to 850℃, keep it warm for 20 minutes, cool it naturally, and collect the ash.
[0054] The ash was ball-milled to obtain rice husk ash with a particle size of 3-6 μm.
[0055] Example 6
[0056] The only difference between this embodiment and embodiment 1 is that rice husk ash is prepared according to the following steps:
[0057] Rice husk and calcium carbonate were mixed in a weight ratio of 100:2, put into a furnace, heated to 450°C, kept warm for 22 minutes, then heated to 650°C, kept warm for 60 minutes, then heated to 800°C, kept warm for 25 minutes, cooled naturally, and the ash was collected.
[0058] The ash was ball-milled to obtain rice husk ash with a particle size of 3-6 μm.
[0059] Example 7
[0060] The only difference between this embodiment and embodiment 1 is that rice husk ash is prepared according to the following steps:
[0061] Rice husk and calcium bicarbonate were mixed in a weight ratio of 100:2, put into a furnace, heated to 450°C, kept warm for 22 minutes, then heated to 650°C, kept warm for 60 minutes, then heated to 800°C, kept warm for 25 minutes, cooled naturally, and the ash was collected.
[0062] The ash was ball-milled to obtain rice husk ash with a particle size of 3-6 μm.
[0063] Example 8
[0064] The only difference between this embodiment and embodiment 1 is that the following raw materials are included: 23 kg fly ash, 12 kg sea silt, 8 kg desulfurized gypsum, 4 kg glass fiber, 13 kg slag, 27 kg cement, 13 kg rice husk ash, and 5 kg diatomaceous earth; the particle size of the slag is 12-15 μm, the particle sizes of sea silt and desulfurized gypsum are 8-10 μm, and the particle sizes of fly ash, rice husk ash, and diatomaceous earth are 3-6 μm.
[0065] In the method for preparing the multi-solid waste-based gelling material of this embodiment:
[0066] Fly ash, sea silt, desulfurized gypsum, slag, cement, rice husk ash and diatomaceous earth are respectively ball-milled to obtain slag with a particle size of 12-15 μm, sea silt and desulfurized gypsum with a particle size of 8-10 μm, and fly ash, rice husk ash and diatomaceous earth with a particle size of 3-6 μm.
[0067] The fly ash, sea silt, desulfurized gypsum, slag, cement, rice husk ash, diatomaceous earth and glass fiber are uniformly mixed to obtain a multi-solid waste-based cementitious material.
[0068] Example 9
[0069] The only difference between this embodiment and embodiment 1 is that the following raw materials are included: 23 kg fly ash, 12 kg sea silt, 8 kg desulfurized gypsum, 4 kg glass fiber, 13 kg slag, 27 kg cement, 13 kg rice husk ash, 5 kg diatomaceous earth, and 5 kg hydroxypropyl methylcellulose ether; the particle size of the slag is 12-15 μm, the particle size of the sea silt and the desulfurized gypsum is 8-10 μm, and the particle size of the fly ash, rice husk ash, and diatomaceous earth is 3-6 μm.
[0070] In the method for preparing the multi-solid waste-based gelling material of this embodiment:
[0071] Fly ash, sea silt, desulfurized gypsum, slag, cement, rice husk ash and diatomaceous earth are respectively ball-milled to obtain slag with a particle size of 12-15 μm, sea silt and desulfurized gypsum with a particle size of 8-10 μm, and fly ash, rice husk ash and diatomaceous earth with a particle size of 3-6 μm.
[0072] The multi-solid waste-based cementitious material is obtained by uniformly mixing fly ash, sea silt, desulfurized gypsum, slag, cement, rice husk ash, diatomaceous earth, hydroxypropyl methylcellulose ether and glass fiber.
[0073] Example 10
[0074] The difference between this embodiment and embodiment 1 is that the present embodiment includes the following raw materials: 23 kg fly ash, 12 kg sea silt, 8 kg desulfurized gypsum, 4 kg glass fiber, 13 kg slag, 27 kg cement, 13 kg rice husk ash, and 2 kg sodium dodecylbenzene sulfonate; the particle size of the slag is 12-15 μm, the particle sizes of the sea silt and the desulfurized gypsum are 8-10 μm, and the particle sizes of the fly ash, rice husk ash, and diatomaceous earth are 3-6 μm.
[0075] In the method for preparing the multi-solid waste-based gelling material of this embodiment:
[0076] Fly ash, sea silt, desulfurized gypsum, slag, cement and rice husk ash are respectively ball-milled to obtain slag with a particle size of 12-15 μm, sea silt and desulfurized gypsum with a particle size of 8-10 μm, and fly ash, rice husk ash and diatomaceous earth with a particle size of 3-6 μm.
[0077] The multi-solid waste-based cementitious material is obtained by uniformly mixing fly ash, sea silt, desulfurized gypsum, slag, cement, rice husk ash, sodium dodecylbenzene sulfonate and glass fiber.
[0078] Embodiment 11
[0079] The difference between this embodiment and embodiment 1 is that the following raw materials are included: 23kg fly ash, 12kg sea silt, 8kg desulfurized gypsum, 4kg glass fiber, 13kg slag, 27kg cement, 13kg rice husk ash, and 2kg bubbling agent; the particle size of the slag is 12-15μm, the particle size of the sea silt and desulfurized gypsum is 8-10μm, and the particle size of the fly ash, rice husk ash, and diatomaceous earth is 3-6μm. The bubbling agent includes aluminum hydroxide, soybean protein powder, and sodium dodecylbenzene sulfonate in a weight ratio of 1:(0.1-0.2):(5-8).
[0080] In the method for preparing the multi-solid waste-based gelling material of this embodiment:
[0081] Fly ash, sea silt, desulfurized gypsum, slag, cement and rice husk ash are respectively ball-milled to obtain slag with a particle size of 12-15 μm, sea silt and desulfurized gypsum with a particle size of 8-10 μm, and fly ash, rice husk ash and diatomaceous earth with a particle size of 3-6 μm.
[0082] Aluminum hydroxide, soybean protein powder and sodium dodecylbenzene sulfonate are uniformly mixed according to a certain proportion to obtain a bubbling agent.
[0083] The fly ash, sea silt, desulfurized gypsum, slag, cement, rice husk ash, bubbling agent and glass fiber are uniformly mixed to obtain a multi-solid waste-based cementitious material.
[0084] Example 12
[0085] The only difference between this embodiment and embodiment 1 is that the multi-solid waste-based cementitious material includes the following raw materials: 23 kg fly ash, 12 kg sea silt, 8 kg desulfurized gypsum, 4 kg glass fiber, 13 kg slag, 27 kg cement, 13 kg rice husk ash, and 1 kg silane coupling agent; the particle size of the slag is 12-15 μm, the particle size of the sea silt and the desulfurized gypsum is 8-10 μm, and the particle size of the fly ash and the rice husk ash is 3-6 μm.
[0086] In the method for preparing a multi-solid waste-based gelling material:
[0087] Fly ash, sea silt, desulfurized gypsum, slag, cement and rice husk ash are respectively ball-milled to obtain slag with a particle size of 12-15 μm, sea silt and desulfurized gypsum with a particle size of 8-10 μm, and fly ash and rice husk ash with a particle size of 3-6 μm.
[0088] The glass fiber and the silane coupling agent are evenly mixed to obtain the surface-modified glass fiber.
[0089] The fly ash, sea silt, desulfurized gypsum, slag, cement, rice husk ash and surface modified glass fiber are uniformly mixed to obtain a multi-solid waste-based cementitious material.
[0090] Embodiment 13
[0091] The difference between this embodiment and embodiment 1 is that the multi-solid waste-based cementitious material includes the following raw materials: 23kg fly ash, 12kg sea silt, 8kg desulfurized gypsum, 4kg glass fiber, 13kg slag, 27kg cement, 13kg rice husk ash, 5kg diatomaceous earth, 5kg hydroxypropyl methylcellulose ether, 2kg bubbling agent, and 1kg silane coupling agent; the particle size of the slag is 12-15μm, the particle size of the sea silt and desulfurized gypsum is 8-10μm, and the particle size of the fly ash and rice husk ash is 3-6μm. Among them, the bubbling agent includes aluminum hydroxide, soy protein powder, and sodium dodecylbenzene sulfonate in a weight ratio of 1:(0.1-0.2):(5-8).
[0092] In the method for preparing a multi-solid waste-based gelling material:
[0093] Fly ash, sea silt, desulfurized gypsum, slag, cement, rice husk ash and diatomaceous earth are respectively ball-milled to obtain slag with a particle size of 12-15 μm, sea silt and desulfurized gypsum with a particle size of 8-10 μm, and fly ash, rice husk ash and diatomaceous earth with a particle size of 3-6 μm.
[0094] Aluminum hydroxide, soybean protein powder and sodium dodecylbenzene sulfonate are uniformly mixed according to a certain proportion to obtain a bubbling agent.
[0095] The glass fiber and the silane coupling agent are evenly mixed to obtain the surface-modified glass fiber.
[0096] The multi-solid waste-based cementitious material is obtained by uniformly mixing fly ash, sea silt, desulfurized gypsum, slag, cement, rice husk ash, diatomaceous earth, hydroxypropyl methyl cellulose ether, bubbling agent and surface-modified glass fiber.
[0097] Comparative Example
[0098] Comparative Example 1
[0099] The only difference between this comparative example and Example 1 is that the particle size of slag is 7-10 μm, the particle size of sea silt and desulfurized gypsum is 4-6 μm, and the particle size of fly ash and rice husk ash is 1-2 μm.
[0100] Comparative Example 2
[0101] The only difference between this comparative example and Example 1 is that the particle size of slag is 16-20 μm, the particle size of sea silt and desulfurized gypsum is 12-15 μm, and the particle size of fly ash and rice husk ash is 7-10 μm.
[0102] Comparative Example 3
[0103] The only difference between this comparative example and Example 1 is that an equal amount of fly ash is used to replace rice husk ash.
[0104] Comparative Example 4
[0105] The only difference between this comparative example and Example 1 is that the sea silt is replaced by an equal amount of fly ash.
[0106] Comparative Example 5
[0107] The only difference between this comparative example and Example 1 is that the glass fiber is replaced by an equal amount of fly ash.
[0108] Performance testing
[0109] The following performance tests were performed on the multi-solid waste-based gelling materials prepared in Examples 1-13 and Comparative Examples 1-5:
[0110] The multi-solid waste-based cementitious material and water were mixed evenly in a weight ratio of 8:2, poured into a mold, and cured in the same environment for 28 days to obtain a test piece with a size of 40mm×40mm×160mm. According to GB17671-1999 "Test Method for Strength of Cement Mortar", the 28d flexural strength and 28d compressive strength of the test piece were tested. According to GB / T208-94 "Determination Method for Density of Cement", the density of the test piece was tested.
[0111] The test results are shown in Table 1.
[0112] Table 1
[0113]
[0114] Combining Example 1 and Comparative Examples 1-5 and Table 1, it can be seen that compared with Example 1, the 28d flexural strength and 28d compressive strength of Comparative Examples 1-5 are significantly reduced, the density of Comparative Examples 1 and 3-5 increases, and the density of Comparative Example 2 decreases. This shows that within the raw material ratio range of Example 1, a multi-solid waste-based cementitious material with a relatively low density and relatively high flexural strength and compressive strength can be obtained. Therefore, the scheme of Example 1 is used to help improve the mechanical properties of solid waste-based cementitious materials.
[0115] Combining Examples 1-3 and Table 1, it can be seen that Examples 1-3 all have higher 28d flexural strength and 28d compressive strength, and the density is 4g / cm 3 This shows that, by using the raw material ratios within the range of Examples 1-3, a multi-solid waste-based cementitious material with a lower density and a higher flexural strength and compressive strength can be obtained.
[0116] Combining Examples 1, 4-7 and Table 1, it can be seen that compared with Example 1, the density of Example 4-7 does not change much, and the 28d flexural strength and 28d compressive strength of Example 4-5 do not change much, but the 28d flexural strength and 28d compressive strength of Example 4-5 are significantly increased. This shows that when preparing rice husk ash, burning rice husk and carbonate or bicarbonate together helps to further enhance the mechanical properties of multi-solid waste-based cementitious materials.
[0117] Combining Examples 1, 8-13 and Table 1, it can be seen that compared with Example 1, the density of Examples 8-9 and 12 does not change much, the density of Examples 10-11 and 13 decreases, and the 28d flexural strength and 28d compressive strength of Examples 8-13 are increased. This shows that when preparing multi-solid waste-based cementitious materials, adding any one of diatomaceous earth, hydroxypropyl methylcellulose ether, bubbling agent and silane coupling agent can help further enhance the mechanical properties of multi-solid waste-based cementitious materials.
[0118] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A multi-solid waste-based cementitious material, characterized in that: The invention comprises the following raw materials in parts by weight: 20-25 parts of fly ash, 10-14 parts of sea silt, 6-10 parts of desulfurized gypsum, 2-5 parts of glass fiber, 12-14 parts of slag, 25-30 parts of cement and 10-15 parts of rice husk ash; the particle size of the slag is 12-15 μm, the particle size of the sea silt and desulfurized gypsum is 8-10 μm, and the particle size of the fly ash and rice husk ash is 3-6 μm.
2. A multi-solid waste-based cementitious material according to claim 1, characterized in that: The rice husk ash is prepared according to the following steps: The rice husk is kept at 400-500°C for 20-25 minutes, heated to 600-700°C, kept for 50-70 minutes, heated to 750-850°C, kept for 20-30 minutes, cooled naturally, and the ashes are collected; The ash was ball-milled to obtain rice husk ash with a particle size of 3-6 μm.
3. A multi-solid waste-based cementitious material according to claim 2, characterized in that: Either carbonate or bicarbonate is mixed evenly with rice husk and then burned at 400-500°C.
4. The multi-solid waste-based cementitious material according to claim 1, characterized in that: The multi-solid waste-based cementitious material also includes diatomaceous earth.
5. The multi-solid waste-based cementitious material according to claim 4, characterized in that: The multi-solid waste-based gelling material also includes cellulose ether.
6. The multi-solid waste-based cementitious material according to claim 1, characterized in that: The multi-solid waste-based gelling material also includes a bubbling agent.
7. The multi-solid waste-based cementitious material according to claim 6, characterized in that: The bubbling agent comprises aluminum hydroxide, soybean protein powder and sodium dodecylbenzene sulfonate in a weight ratio of 1:(0.1-0.2):(5-8).
8. The multi-solid waste-based cementitious material according to claim 1, characterized in that: The multi-solid waste-based gelling material also includes a silane coupling agent.
9. A method for preparing a multi-solid waste-based cementitious material according to any one of claims 1 to 8, characterized in that: The steps include: The fly ash, sea silt, desulfurized gypsum, slag, cement and rice husk ash are respectively ball-milled to obtain slag with a particle size of 12-15 μm, sea silt and desulfurized gypsum with a particle size of 8-10 μm, and fly ash and rice husk ash with a particle size of 3-6 μm; The fly ash, sea silt, desulfurized gypsum, slag, cement, rice husk ash and glass fiber are evenly mixed to obtain a multi-solid waste-based cementitious material.
Citation Information
Cited By
Solid waste-based self-repairing functional filler and preparation method thereof
CN121377591A